(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
BKPyV, a small DNA virus classified into the polyomaviridaefamily, is holoendemic with global distributionamong human population.The objective of this study is to determine the prevalence of anti-BK polyomavirusIgG antibodies among cancer patients and healthy controls. In the present study, A total of 85 serum sampleswere collected (65 cancer patients and 20 healthy controls) with age range between 15- 75 years, the femaleto-male ratio was 3:1. All obtained sera samples were tested using ELISA method for the detection ofanti-BK polyomavirus IgG antibodies. BKV-IgG seroprevalence show high rate of exposure to the virus48.23% (41 of 85 samples) revealed positive result (50.77% in cancer patient and 40% in healthy control).Seroprevalence was not different between female and male. The frequency of IgG antibodies decreased from66.67% in the age group <40 years to 46.94% among age group 40-60 years, and drop again to 38.1% in>60 years old.